Synthesis and structure-activity relationships of novel 5-(hydroxamic acid)methyl oxazolidinone derivatives as 5-lipoxygenase inhibitors - Oludotun A. Phillips; Mira A. Bosso; Charles I. Ezeamuzie (Taylor & Francis Group, 2020)
Oxazolidinone hydroxamic acid derivatives were synthesised and evaluated for inhibitory activity against leukotriene (LT) biosynthesis in three in vitro cell-based test systems and on direct inhibition of recombinant human 5-lipoxygenase (5-LO). Thirteen of the 19 compounds synthesised were considered active ((50% inhibitory concentration (IC50) ≤ 10 µM in two or more test systems)). Increasing alkyl chain length on the hydroxamic acid moiety enhanced activity and morpholinyl-containing derivatives were more active than N-acetyl-piperizinyl derivatives. The IC50 values in cell-based assay systems were comparable to those obtained by direct inhibition of 5-LO activity, confirming that the compounds are direct inhibitors of 5-LO. Particularly, compounds PH-249 and PH-251 had outstanding potencies (IC50 < 1 µM), comparable to that of the prototype 5-LO inhibitor, zileuton. Pronounced in vivo activity was demonstrated in zymosan-induced peritonitis in mice. These novel oxazolidinone hydroxamic acid derivatives are, therefore, potent 5-LO inhibitors with potential application as anti-allergic and anti-inflammatory agents.